Terrestrial and aquatic mollusks as environmental indicators at the Brogley Rockshelter, Grant County, Wisconsin - Harms, Sheena (My University, 2008)
The Brogley rockshelter (47Gt156) is an archaeological site located in southwestern Wisconsin's Driftless Area. It has both an Archaic and Woodland human occupation which, after excavation, resulted in the discovery of a wealth of artifacts and floral, faunal, and aquatic assemblages. Recently, MVAC received sediment samples from a series of units at Brogley rockshelter, permitting a comprehensive analysis of selected site materials. My thesis will contribute an important part to this analysis. It focuses on the aquatic and terrestrial mollusks found in the sediment samples. By analyzing the variety of species from two different samples, and carbon dating each, the environmental fluctuations in the area, along with their respective time period, can be approximated.
Keywords: Grant County (Wis.) -- Antiquities; Brogley Rockshelter (Wis.); Environmental indicators -- Wisconsin -- Grant County; Mollusks, Fossil -- Wisconsin -- Grant County